Преобразовать выражение: (sin²β+tg²β*sin²β)*ctgβ

anyutkavolf20 anyutkavolf20    2   03.07.2019 01:40    0

Ответы
vorontsovaksus vorontsovaksus  02.10.2020 18:58
(sin^2\beta+tg^2\beta*sin^2\beta)*ctg\beta\\(sin^2\beta+\frac{sin^2\beta}{cos^2\beta}*sin^2\beta)*\frac{cos\beta}{sin\beta}=sin\beta cos\beta+\frac{sin^3\beta}{cos\beta}=\frac{sin\beta cos^2\beta + sin^3\beta}{cos\beta}=\\=\frac{sin\beta(cos^2\beta+sin^2\beta)}{cos\beta}=tg\beta

К сведению:
sin^2\alpha+cos^2\alpha = 1 
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра